Dialectics of Media, Critique of Image, and Construction of the World: Three Faces of Vilém Flusser’s Technical Image Theory - Li, Siyang (Actual Problems of Theory and History of Art, 2024)
Vilém Flusser’s theory of technical images delved deeply into the ethical values of technical images in post-industrial society and their impact on the development of human civilization. This paper holds that technical images, emerging as a new possibility following the crises of traditional images and linear texts, play a crucial role in reshaping our understanding of the world, influencing human behavior, and altering social structures. Flusser’s theory provides a perspective on constructing an ideal world of technical images through political dialogic reform, the development of immaterial culture, and the defense of human creativity. By emphasizing the double-edged nature of technical images, Flusser calls for an awareness of the responsibility in defending human subjectivity and promoting ethical social practices. This paper further explores how technical images, through the ethical dimensions of dialogue and coexistence, can build a more humane world and a new world order based on information and dialogue, offering a solution to the ethical challenges of post-industrial society. Furthermore, the paper underscores that in the epoch of technical images, humans should achieve a new mode of coexistence with the world through creative play and artistic actions with technical images.
Keywords: Vilém Flusser; technical image; dialectics of media; critique of image; construction of the world; post-history